2021
DOI: 10.1093/ckj/sfab291
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibody response to SARS-CoV-2 after two doses of inactivated virus and BNT162b2 mRNA vaccines in kidney transplant

Abstract: Background Antibody response against SARS-CoV-2 after mRNA or adenoviral vector based vaccines is weak in kidney transplant (KT) patients. However, few studies have focused on humoral response after inactivated virus-based vaccines in KT. Here, we compare antibody response following vaccination with inactivated virus (Coronavacࣨ) and BNT162b2 mRNA. Methods A national multicenter cross-sectional study was conducted. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…In the current study, we confirmed that a lower Davies Comorbidity Score correlates to higher antibody levels. In accordance with recently published data on patients after kidney transplantation (17) and those with diabetes (18), our mixed model analysis for repeated measurement identified a higher GFR to be associated with higher antibody levels in PD patients. Impairment of kidney function as well as the presence of co-morbidities have been reported as factors altering the immune system and influencing immune responses to vaccines and pathogens (3,19).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, we confirmed that a lower Davies Comorbidity Score correlates to higher antibody levels. In accordance with recently published data on patients after kidney transplantation (17) and those with diabetes (18), our mixed model analysis for repeated measurement identified a higher GFR to be associated with higher antibody levels in PD patients. Impairment of kidney function as well as the presence of co-morbidities have been reported as factors altering the immune system and influencing immune responses to vaccines and pathogens (3,19).…”
Section: Discussionsupporting
confidence: 89%
“…BNT162b2 and CoronaVac are well tolerated and protective against COVID-19 in healthy adults. However, in kidney transplant recipients, mRNA based BNT162b2 has been shown to induce a higher nucleocapsid antibody response and T cell response than the inactivated vaccine, CoronoVac [17] . Also, the antibody response persists longer in BNT162b2 and is more effective against the omicron variant than the CoronoVac in healthy population [18] .…”
Section: Discussionmentioning
confidence: 99%
“…The lower antibody titers elicited by inactivated virus vaccines would be of even greater clinical concern for certain vulnerable groups of patients. For example, in immunosuppressed kidney transplant patients, the response to the different types of vaccine also showed a similar pattern, with 36.5%/27.8% of patients seroconverting post-mRNA/inactivated virus vaccination, with greater post-mRNA vaccination antibody levels (median 173 (mRNA) and 29 (inactivated virus) BAU/mL, p < 0.034) [ 24 ]. Similarly, in a study examining multiple sclerosis patients treated with disease modifying therapy, the inactivated vaccine only resulted in a seroconversion rate of 64.9%, much less than the 81.2% seroconversion rate of the mRNA vaccine [ 25 ].…”
Section: Discussionmentioning
confidence: 99%